THE VAMPIRLIJA HILL IN THE VILLAGE OF MIJAJLOVAC (TRSTENIK): A POSSIBLE LOCATION FOR THE BIRTHPLACE OF EUROPEAN ‘VAMPIROLOGY’ - ALEKSANDAR RISTIĆ (Faculty of Philosophy Novi Sad, Department of History, 2021)
Vampires gained worldwide popularity due to the classic novel about the most famous one, Dracula, written by Bram Stoker in 1897. Bram Stoker’s Dracula has very little in common with his inspiration, the fifteenth-century Wallachian ruler Vlad III (1431‒1476), who was a real historical figure. However, some strange events involving the dead seem to have occurred in Southwest of Transylvania a few centuries after the Wallachian prince’s death. In some parts of the Habsburg Kingdom of Serbia (1718‒1739), the local Austrian authorities recorded some cases of ‘vampirism’, which Europe would be introduced to shortly afterward, along with this newly accepted word. This paper will present historical facts about one particular case recorded at the southernmost border of the Habsburg Empire, which at the time was the West Morava River. It was the case of a ‘vampire’ named Arnold Paole, who died in 1726/7 in the border village of Medveđa and whose case ‘infected’ the whole Europe with the ‘virus’ of ‘vampiromania’. The main goal of the paper is to locate the spot where one of the first ‘vampire slayings’ ever recorded could have taken place, and to direct further investigations within early modern age archaeology.